Comparison of cellular localisation of the Ca2+‐binding proteins calbindin, calretinin and parvalbumin in the retina of four different Macaca species. (28th August 2018) - Roski, Christian; Langrock, Christiane; Körber, Nicole; Habermann, Gunnar; Buse, Eberhard; Reichenbach, Andreas; Pannicke, Thomas; Francke, Mike
Abstract: Ca 2+ ‐binding proteins are differentially expressed in the nervous system; their functional role often remains unclear. This immunohistochemical study aimed at characterising and comparing the expression pattern of the Ca 2+ ‐binding proteins calbindin (Calb), calretinin (Calr) and parvalbumin (Parv) in the retina of four species of macaque monkeys: Macaca fascicularis (cynomolgus macaque), M. mulatta (rhesus macaque), M. thibetana (Tibetan macaque) and M. fuscata (Japanese macaque). Calb was found in cone photoreceptors and in a subset of bipolar cells. Calr was expressed in a subpopulation of amacrine cells. Parv was present in horizontal and ganglion cells. In addition, Müller cells were stained using antibodies against the specific marker cellular retinaldehyde‐binding protein (CRALBP). Immunostainings were used for calculation of the density of different cell populations. The expression pattern was similar between the examined species and between retinal regions.